Morphological evidence of sexual dimorphism in a Continental anole species of southeastern of Mexico - Luis Manuel Badillo Saldaña; AARÓN GARCÍA-ROSALES; J. DANIEL LARA-TUFIÑO; AURELIO RAMÍREZ-BAUTISTA (Society for Indonesian Biodiversity, 2019)
Abstract. Badillo-Saldaña LM, García-Rosales A, Lara-Tufiño JD, Ramírez-Bautista A. 2019. Morphological evidence of sexual dimorphism in a Continental anole species of southeastern Mexico. Biodiversitas 20: 3347-3351. Intersexual differences (sexual dimorphism; SD) have been observed in many traits of vertebrate and invertebrate species. These differences evolved as a response to ecological factors, such as the display of morphological and behavioral attributes during reproduction, territorial defense, or differential use of resources. However, some species of lizards do not show high SD, as is the case of some slender small body-sized anoles of the Caribbean Islands. Despite extensive knowledge about SD in island anoles, SD has not been evaluated for most mainland species. Therefore, the goal of this study was to evaluate the SD of a small body-sized species (Anolis unilobatus) throughout its distribution in Mexico, making use of eight morphological characteristics and multivariate analyses. The results showed that snout-vent (SVL) and forearm (FAL) lengths of males are larger than those of females. This could be explained by males being more territorial, so larger size will make them more successful in defending their territory from other males. Therefore, the difference in SVL and FAL between males and females of this species could be related to defense of their territory. The differences observed in morphological structures between males and females could thus support the hypothesis of sexual selection.